Budidaya Ikan Jelawat (Leptobarbus hoevenii) Berdasarkan Sistem Keramba di Sungai Kampar - Syamsul Bachry; Febri Ayu; Andi Saputra (Journal of Engineering Science and Technology Management (JES-TM), 2021)
Kampar River is one of the largest rivers in Riau Province which has been developed for aquaculture with a cage system. This study aims to determine the cultivation and marketing of jelawat fish. The method in this research is to collect primary and secondary data through sources of information from the people who have cages. The results showed that the cage business carried out by the community was through the stages of hatchery, enlargement and marketing of production results. The feasibility study of the cage business shows that the environmental aspects of aquatic ecosystems and marketing aspects are very important. However, the feed factor and business capital are the most important factors in conducting cage cultivation business in Air Tiris